(untitled) (International journal of artificial intelligence, 2026)
This article provides a comprehensive comparative analysis of the grammatical systems of the Japanese and Uzbek languages.The study examines morphological, syntactic, semantic and pragmatic features, including word structure,affixation systems,word order,tense and mood categories and honorific expressions.Special attention is given to the agglutinative nature of both languages, demonstrating how grammatical meanings are formed through the attachment of affixes to word stems.The paper also analyzes similarities and differences in SOV (Subject–Object–Verb) word order,as well as contrasts in writing systems,including Japanese hiragana, katakana, kanji, and the Uzbek Latin alphabet.Furthermore,the study highlights contextual dependency in Japanese compared to the relatively explicit grammatical structure of Uzbek.Overall,this research contributes to comparative linguistics by identifying structural similarities and differences between the two languages.